USING COLLABORATIVE WRITING IN TEACHING WRITING - Sukirman Sukirman (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Collaborative writing strategy is a kind of writing that involves a number of persons. This strategy has a number of advantages as well disadvantages. For the advantages; promotes; 1) social skills development; 2) stress reduction and time-saving benefits; 3) motivational effects; 4) improvement in the content of their writing; and 5) gains in grammatical and structural proficiency. Then, the disadvantages deal with; 1) increases stress; 2) logistical problems; 3) target language usage; 4) a conflict with personal learning style; and 5) issues of fairness. This writing also provides an example how to use collaborative writing in teaching cause/effect essay by presenting the teaching procedures starting from pre-writing until post-writing. Finally, the writer also provides rubrics that can be used by the teachers in assessing their students writing.